Catalyst for recycling waste FCC and its preparation method and application
By synthesizing carbon/phosphorus doped porous graphite phase carbon nitride with waste FCC catalyst as a template, the problem of low economic benefits of waste FCC catalyst is solved, and its in-depth utilization and high-value photocatalytic activity are achieved.
Patent Information
- Application Number
- CN202310585414.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-23
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-05-23
AI Technical Summary
The prior art has low economic benefits when utilizing waste FCC catalysts and fails to fully realize its value.
By using the waste FCC catalyst with the Y-type molecular sieve structure as a template, the organic impurities deposited on the surface are removed, the cage-like structure is destroyed to form an aluminum-silicon chain structure, and the surface is modified by phospholipid film, and then mixed with the graphite-like phase carbon nitride precursor, and carbon/phosphorus-doped porous graphite-like phase carbon nitride is synthesized through calcination and acid etching.
The in-depth utilization of waste FCC catalyst has been achieved, and the synthetic porous graphite phase carbon nitride has excellent photocatalytic activity and high economic value.
Abstract
Description
Technical Field
[0001] The invention relates to a high-value resource utilization method for waste catalysts, and in particular to the field of waste FCC catalyst recycling and graphite-like phase carbon nitride synthesis. Background Art
[0002] Since the 21st century, with the rapid development of the economy, the demand for oil has been increasing. At present, my country has become the world's second largest oil consumer. With the strengthening of environmental protection awareness, people's demand for light oil is also increasing. Fluidized catalytic cracking (FCC) catalysts are widely used in modern petroleum refining industry due to their excellent activity, heavy metal resistance, activity stability, residual oil cracking performance, gasoline selectivity and low cost. According to statistics, as of 2020, my country's refining capacity has exceeded 900 million tons. In the process of petroleum refining catalysis, FCC catalysts will be deactivated due to the combined effects of sintering, pollution of heavy metals Ni, V, Fe, pulverization and hydrothermal effects. According to the standards of my country's refining industry, 0.354kg of waste FCC catalyst will be produced for every ton of crude oil refining. Based on this estimate, more than 100,000 tons of waste FCC catalysts are produced in my country each year.
[0003] At present, the main utilization methods of waste FCC catalysts can be divided into three categories: one is to use it as an adsorbent to absorb harmful substances and metal ions in wastewater; the second is to use it as an adsorbent to be added to white clay to refine lubricating oil base oil and FCC diesel; the third is to replace part of the white clay as an adsorbent to refine paraffin. Of course, since the waste FCC catalyst contains about 3-8% rare earth (mainly La2O3 and CeO2), it is almost the same as the rare earth content in some ores. Therefore, there are also treatment measures to extract rare earth elements from waste FCC catalysts for recycling, which can not only bring huge economic benefits, but also save the mining of primary rare earth mineral resources. At present, the most common technology for extracting rare earth elements from waste FCC catalysts is acid extraction technology, that is, using strong acid to dissolve the metal elements in the catalyst, and then separating and purifying them. This method is simple to operate and has a high recovery rate. For example, patents CN111378842B, CN112695213B, and CN111690811A all use acid extraction technology, and the recovery rate of rare earth elements can reach more than 95%.
[0004] However, the use of acid extraction technology to extract rare earth elements from spent FCC catalysts does not fully realize the value of spent FCC catalysts. FCC catalyst is a Y-type molecular sieve, which is not only a good catalyst material, but also an excellent template material due to its porous and large specific surface area. During use, FCC catalysts are deactivated due to the deposition of coke and heavy metals on the catalyst surface and the collapse of some pores, but the overall structure of the catalyst is not destroyed and it still has value as a template. Summary of the invention
[0005] The purpose of the present invention is to provide a method for recycling waste FCC catalysts in order to solve the problem that the current recycling method of waste FCC catalysts is single and has low economic benefits; another purpose of the present invention is to provide a method for high-value resource utilization of waste catalysts.
[0006] The technical route of the present invention is: using the waste FCC catalyst with Y-type molecular sieve structure as template, removing organic impurities deposited on its surface through pretreatment, destroying the cage structure to form an aluminum silicon chain structure, and then modifying the surface of the aluminum silicon chain so that the surface has a layer of phospholipid membrane, and the phospholipid membrane has the following functions: 1) avoiding direct contact between the graphite-like carbon nitride precursor and the waste FCC catalyst, thereby preventing heavy metal pollution on the surface of the waste FCC catalyst; 2) phosphorus and carbon elements generated by the decomposition of the phospholipid membrane at high temperature enter the graphite-like carbon nitride structure to form doping; 3) expanding the pore size of the graphite-like carbon nitride. Finally, the mixture of the template and the precursor is calcined, and the template is removed by acid etching to obtain the carbon / phosphorus doped porous graphite-like carbon nitride.
[0007] A catalyst for resource utilization of waste FCC, which uses treated waste FCC catalyst as a template, cyanamide compounds as a precursor, and phospholipids as a surface modifier to synthesize carbon / phosphorus-doped porous graphite-like carbon nitride through a calcination method, wherein the mass ratio of the template to the precursor is 0.1 to 10:1.
[0008] In the technical solution of the present invention: the mass ratio of the template to the precursor is 0.5 to 3:1.
[0009] A method for preparing the above catalyst, the specific steps of the method are as follows:
[0010] (1) Pretreatment of spent FCC catalyst:
[0011] a. Ball-mill the spent FCC catalyst and screen the fine powder below 100 mesh; calcine to remove the coke and other organic impurities adsorbed on the surface;
[0012] b. The powder obtained in step a and the structure destroying agent are dispersed in deionized water, ultrasonically shaken for 1 to 2 hours, and then stirred and dried at 80°C; the resulting mixture is then calcined at 500 to 600°C for 2 to 4 hours under a N2 atmosphere, and the calcined product is washed with water and dried for later use;
[0013] c. The powder obtained in step b is dispersed in the phospholipid solution and stirred for 2 to 4 hours, and then the lower layer of powder is removed by centrifugation, rinsed, and dried for later use;
[0014] (2) Precursor and template mixing: The waste FCC catalyst powder pretreated in step (1) and the graphite-like carbon nitride precursor are dispersed in 50-100° C. deionized water and stirred into a paste;
[0015] (3) calcining the mixture: calcining the paste mixture obtained in step (2) to obtain a mixture of porous graphite-like carbon nitride and the template;
[0016] (4) Template primary etching: The mixture obtained in step (3) is dispersed in an excess of acid solution and stirred for 8 to 12 hours, and then centrifuged and washed to remove the template and heavy metal elements to obtain sample 1;
[0017] (5) Secondary etching of the template: Sample 1 was dispersed in an excess of hydrofluoric acid solution and stirred for 8 to 12 hours to completely remove the template, and then centrifuged, washed and dried to obtain a carbon / phosphorus doped porous graphite-like carbon nitride.
[0018] In the above preparation method: the conditions for pretreatment of the waste FCC catalyst are as follows:
[0019] In step a, the calcination environment is an oxygen-rich condition, the calcination temperature is 500-600° C., and the calcination time is 2-4 hours.
[0020] The structural destructing agent in step b is ammonium chloride or ammonium sulfate, and the mass ratio of the structural destructing agent to the powder is 0.5 to 3:1;
[0021] The phospholipid solution described in step c is a saturated phosphatidylcholine solution using ethanol as a solvent.
[0022] In the above preparation method: the graphite-like carbon nitride precursor in step (2) is one of cyanamide, dicyandiamide and melamine, and the mass ratio of the graphite-like carbon nitride precursor to deionized water is 1:40-60.
[0023] In the above preparation method: the temperature of deionized water in step (2) is 60-80°C.
[0024] In the above preparation method: the calcination temperature in step (3) is 500-600° C., the calcination time is 2-4 hours, and the calcination condition is air atmosphere.
[0025] In the above preparation method: in step (4), the acid solution in the primary etching process of the template agent is a 1-5M hydrochloric acid or nitric acid solution, and in step (5), the hydrofluoric acid solution is a 1-5M hydrofluoric acid solution.
[0026] In the technical solution of the present invention, the catalyst is used in degrading organic matter.
[0027] Beneficial effects: The present invention is an extension of the application of extracting rare earth elements from waste FCC catalysts. Before the traditional acid extraction of rare earth elements, the waste FCC catalyst is used as a template to synthesize carbon / phosphorus doped porous graphite-like carbon nitride, and then the template etching liquid is collected, separated, and the rare earth elements are purified to achieve in-depth utilization of waste FCC catalysts. The steps are simple, and the synthesized porous graphite-like carbon nitride has excellent photocatalytic activity and high economic value. DETAILED DESCRIPTION
[0028] The present invention is further described below in conjunction with the embodiments, but the protection scope of the present invention is not limited thereto: Embodiment 1
[0029] (1) Pretreatment: ball-mill the spent FCC catalyst and screen the fine powder below 100 mesh, then calcine at 500°C for 2 h, continuously introducing air during the calcination; weigh 10 g of the calcined fine powder and 5 g of ammonium chloride, disperse them in 50 ml of deionized water, ultrasonically vibrate for 1 h, and then stir to dry at 80°C; calcine the obtained sample at 500°C in a N2 atmosphere for 2 h, then wash it with water three times and dry it for use; disperse the reserve sample in 100 ml of a saturated phosphatidylcholine solution and stir it for 2 h, then centrifuge to remove the lower layer of powder, rinse it with anhydrous ethanol, and dry it to obtain 7.71 g of powder for use.
[0030] (2) Precursor and template mixing: 10 g of cyanamide and 5 g of treated waste FCC catalyst powder were weighed and dispersed in 500 ml of deionized water. After stirring at 60° C. for 2 h, the mixture was stirred and dried into a paste.
[0031] (3) calcining the mixture: calcining the paste mixture in an air atmosphere at 500° C. for 2 h to obtain a mixture of porous graphite-like carbon nitride and the template;
[0032] (4) Template primary etching: The mixture obtained in step (3) was dispersed in 500 ml of 1M HCl solution and stirred for 8 h, and then centrifuged to remove the template and heavy metal elements to obtain sample 1, and the centrifuged washing liquid was recovered;
[0033] (5) Secondary etching of the template: The sample was then dispersed in 500 ml of 1 M HF solution and stirred for 8 h to completely remove the template, followed by centrifugal washing and drying to obtain porous graphite-like carbon nitride.
[0034] (6) Catalyst performance test: The photocatalytic performance of porous graphite-like carbon nitride was characterized by photocatalytic degradation of rhodamine B. A 10 mg / L rhodamine B solution was prepared, 100 mg of porous graphite-like carbon nitride was weighed and dispersed in 100 ml of rhodamine B solution, stirred for 60 min in the dark, and then placed under visible light (λ≥420 nm) for 60 min. The rhodamine degradation rate was 93.8%.
[0035] Example 2
[0036] (1) Pretreatment: Ball mill the spent FCC catalyst and screen the fine powder below 100 mesh, then calcine at 550°C for 3 h, while continuously introducing air; weigh 15 g of the calcined fine powder and 15 g of ammonium sulfate, disperse them in 200 ml of deionized water, ultrasonically vibrate for 1.5 h, and then stir to dry at 80°C; calcine the obtained sample at 550°C in a N2 atmosphere for 3 h, then wash it with water three times and dry it for use; disperse the reserve sample in 100 ml of a saturated phosphatidylcholine solution and stir it for 3 h, then centrifuge to remove the lower layer of powder, rinse it with anhydrous ethanol, and dry it to obtain 11.68 g of powder for use.
[0037] (2) Precursor and template mixing: 10 g of dicyandiamide and 10 g of treated waste FCC catalyst powder were dispersed in 500 ml of deionized water, stirred at 80° C. for 4 h, and then dried to a paste.
[0038] (3) calcining the mixture: calcining the paste mixture in an air atmosphere at 550° C. for 3 h to obtain a mixture of porous graphite-like carbon nitride and the template;
[0039] (4) Template primary etching: The mixture obtained in step (3) was dispersed in 500 ml of 3M HNO3 solution and stirred for 10 h, and then centrifuged to remove the template and heavy metal elements to obtain sample 1, and the centrifuged washing liquid was recovered;
[0040] (5) Secondary etching of the template: The sample was then dispersed in 500 ml of 3M HF solution and stirred for 10 h to completely remove the template, followed by centrifugal washing and drying to obtain porous graphite-like carbon nitride.
[0041] (6) Catalyst performance test: The photocatalytic performance of porous graphite-like carbon nitride was characterized by photocatalytic degradation of rhodamine B. A 10 mg / L rhodamine B solution was prepared, 100 mg of porous graphite-like carbon nitride was weighed and dispersed in 100 ml of rhodamine B solution, stirred for 60 min in the dark, and then placed under visible light (λ≥420 nm) for 50 min. The rhodamine degradation rate was 95.6%.
[0042] Example 3
[0043] (1) Pretreatment: ball-mill the spent FCC catalyst and screen the fine powder below 100 mesh, then calcine at 600°C for 4 h, continuously introducing air during the calcination; weigh 25 g of the calcined fine powder and 50 g of ammonium sulfate, disperse them in 300 ml of deionized water, ultrasonically vibrate for 2 h, and then stir to dry at 80°C; calcine the obtained sample at 550°C in a N2 atmosphere for 4 h, then wash it with water three times and dry it for use; disperse the reserve sample in 150 ml of a saturated phosphatidylcholine solution and stir it for 3 h, then centrifuge to remove the lower layer of powder, rinse it with anhydrous ethanol, and dry it to obtain 23.52 g of powder for use.
[0044] (2) Precursor and template mixing: 10 g of melamine and 20 g of treated waste FCC catalyst powder were weighed and dispersed in 500 ml of deionized water. After stirring at 70° C. for 2 h, the mixture was stirred and dried into a paste.
[0045] (3) calcining the mixture: calcining the paste mixture in an air atmosphere at 600° C. for 4 h to obtain a mixture of porous graphite-like carbon nitride and the template;
[0046] (4) Template primary etching: The mixture obtained in step (3) was dispersed in 600 ml of 5M HCl solution and stirred for 12 h, and then centrifuged and washed to remove the template and heavy metal elements to obtain sample 1, and the centrifuged washing liquid was recovered;
[0047] (5) Secondary etching of the template: The sample was then dispersed in 600 ml of 5 M HF solution and stirred for 12 h to completely remove the template, followed by centrifugal washing and drying to obtain porous graphite-like carbon nitride.
[0048] (6) Catalyst performance test: The photocatalytic performance of porous graphite-like carbon nitride was characterized by photocatalytic degradation of rhodamine B. A 10 mg / L rhodamine B solution was prepared, 100 mg of porous graphite-like carbon nitride was weighed and dispersed in 100 ml of rhodamine B solution, stirred for 60 min in the dark, and then placed under visible light (λ≥420 nm) for 45 min. The rhodamine degradation rate was 99.2%.
[0049] Example 4
[0050] (1) Pretreatment: ball-mill the spent FCC catalyst and screen the fine powder below 100 mesh, then calcine at 600°C for 4 h, during which air is continuously introduced; weigh 40 g of the calcined fine powder and 120 g of ammonium chloride, disperse them in 150 ml of deionized water, ultrasonically vibrate for 2 h, and then stir to dry at 80°C; calcine the obtained sample at 600°C in a N2 atmosphere for 4 h, then wash it with water three times and dry it for use; disperse the reserve sample in 100 ml of a saturated phosphatidylcholine solution and stir it for 4 h, then centrifuge to remove the lower layer of powder, rinse it with anhydrous ethanol, and dry it to obtain 33.61 g of powder for use.
[0051] (2) Precursor and template mixing: 10 g of dicyandiamide and 30 g of treated waste FCC catalyst powder were dispersed in 500 ml of deionized water, stirred at 80° C. for 4 h, and then dried to a paste.
[0052] (3) calcining the mixture: calcining the paste mixture in an air atmosphere at 600° C. for 4 h to obtain a mixture of porous graphite-like carbon nitride and the template;
[0053] (4) Template primary etching: The mixture obtained in step (3) was dispersed in 1000 ml of 5M HNO3 solution and stirred for 12 h, and then centrifuged to remove the template and heavy metal elements to obtain sample 1, and the centrifuged washing liquid was recovered;
[0054] (5) Secondary etching of the template: The sample was then dispersed in 1000 ml of 5 M HF solution and stirred for 12 h to completely remove the template, followed by centrifugal washing and drying to obtain porous graphite-like carbon nitride.
[0055] (6) Catalyst performance test: The photocatalytic performance of porous graphite-like carbon nitride was characterized by photocatalytic degradation of rhodamine B. A 10 mg / L rhodamine B solution was prepared, 100 mg of porous graphite-like carbon nitride was weighed and dispersed in 100 ml of rhodamine B solution, stirred for 60 min under dark conditions, and then placed under visible light (λ≥420 nm) for reaction for 60 min. The rhodamine degradation rate was 91.7%.
[0056] Comparative Example 1
[0057] Weigh 10g of melamine and calcine it at 550℃ for 3h in air atmosphere to obtain agglomerated graphite-like carbon nitride. Prepare 10mg / L rhodamine B solution, weigh 100mg of agglomerated graphite-like carbon nitride and disperse it in 100ml rhodamine B solution, stir it for 60min under dark conditions, and then place it under visible light (λ≥420nm) to react for 60min. The rhodamine degradation rate is 29.6%.
[0058] Comparative effect: Compared with the graphite-like carbon nitride without pores, the carbon / phosphorus-doped porous graphite-like carbon nitride synthesized using waste FCC catalyst as a template has significantly improved effect.
[0059] Comparative Example 2
[0060] (1) Pretreatment: Ball mill the spent FCC catalyst and screen out fine powders below 100 mesh. Then weigh 25 g of the powder and calcine it at 600°C for 4 h, while continuously introducing air. Disperse the sample for later use in 150 ml of saturated phosphatidylcholine solution and stir for 3 h. Then centrifuge to remove the lower layer of powder, rinse it with anhydrous ethanol, and dry it to obtain 24.19 g of powder for later use.
[0061] (2) Precursor and template mixing: 10 g of melamine and 20 g of treated waste FCC catalyst powder were weighed and dispersed in 500 ml of deionized water. After stirring at 70° C. for 2 h, the mixture was stirred and dried into a paste.
[0062] (3) calcining the mixture: calcining the paste mixture in an air atmosphere at 600° C. for 4 h to obtain a mixture of porous graphite-like carbon nitride and the template;
[0063] (4) Template primary etching: The mixture obtained in step (3) was dispersed in 600 ml of 5M HCl solution and stirred for 12 h, and then centrifuged and washed to remove the template and heavy metal elements to obtain sample 1, and the centrifuged washing liquid was recovered;
[0064] (5) Secondary etching of the template: The sample was then dispersed in 600 ml of 5 M HF solution and stirred for 12 h to completely remove the template, followed by centrifugal washing and drying to obtain porous graphite-like carbon nitride.
[0065] (6) Catalyst performance test: The photocatalytic performance of porous graphite-like carbon nitride was characterized by photocatalytic degradation of rhodamine B. A 10 mg / L rhodamine B solution was prepared, 100 mg of porous graphite-like carbon nitride was weighed and dispersed in 100 ml of rhodamine B solution, stirred for 60 min in the dark, and then placed under visible light (λ≥420 nm) for 60 min. The rhodamine degradation rate was 72.4%.
[0066] Comparative effect: The carbon / phosphorus doped porous graphite-like carbon nitride synthesized with the waste FCC catalyst without destroying the waste structure and only undergoing surface modification as the template has a degradation efficiency of 72.4% for rhodamine in 60 minutes. Compared with comparative example 1, the activity is significantly improved, but the efficiency is significantly reduced compared with the example.
[0067] Comparative Example 3
[0068] (1) Pretreatment: Ball mill the spent FCC catalyst and screen out fine powders below 100 mesh, then calcine at 600°C for 4 h, with air continuously introduced; weigh 25 g of the calcined fine powder and 50 g of ammonium sulfate, disperse them in 300 ml of deionized water, ultrasonically vibrate for 2 h, and stir to dry at 80°C; calcine the obtained sample at 550°C in a N2 atmosphere for 4 h, then wash with water three times and dry to obtain 24.03 g of powder for use.
[0069] (2) Precursor and template mixing: 10 g of melamine and 20 g of treated waste FCC catalyst powder were weighed and dispersed in 500 ml of deionized water. After stirring at 70° C. for 2 h, the mixture was stirred and dried into a paste.
[0070] (3) calcining the mixture: calcining the paste mixture in an air atmosphere at 600° C. for 4 h to obtain a mixture of porous graphite-like carbon nitride and the template;
[0071] (4) Template primary etching: The mixture obtained in step (3) was dispersed in 600 ml of 5M HCl solution and stirred for 12 h, and then centrifuged and washed to remove the template and heavy metal elements to obtain sample 1, and the centrifuged washing liquid was recovered;
[0072] (5) Secondary etching of the template: The sample was then dispersed in 600 ml of 5 M HF solution and stirred for 12 h to completely remove the template, followed by centrifugal washing and drying to obtain porous graphite-like carbon nitride.
[0073] (6) Catalyst performance test: The photocatalytic performance of porous graphite-like carbon nitride was characterized by photocatalytic degradation of rhodamine B. A 10 mg / L rhodamine B solution was prepared, 100 mg of porous graphite-like carbon nitride was weighed and dispersed in 100 ml of rhodamine B solution, stirred for 60 min in the dark, and then placed under visible light (λ≥420 nm) for 60 min. The rhodamine degradation rate was 65.3%.
[0074] Comparative effect: The efficiency of rhodamine degradation in 60 minutes by using porous graphite-like carbon nitride synthesized by template using waste FCC catalyst with destroyed structure and no surface modification is 65.3%. Compared with comparative example 1, the activity is significantly improved, and the efficiency is significantly reduced compared with the example.
Claims
1. A catalyst for recycling waste FCC, characterized by: The catalyst uses the treated waste FCC catalyst as a template, cyanamide compounds as a precursor, and phospholipids as a surface modifier to synthesize carbon / phosphorus-doped porous graphite-like carbon nitride by a calcination method, wherein the mass ratio of the template to the precursor is 0.1-10:
1. The steps for pretreatment of spent FCC catalyst are as follows: a. Ball-mill the spent FCC catalyst and screen the fine powder below 100 mesh; calcine to remove the coke and other organic impurities adsorbed on the surface; b. The powder obtained in step a and the structure destroying agent are dispersed in deionized water, ultrasonically shaken for 1 to 2 hours, and then stirred and dried at 80 ° C; the resulting mixture is then calcined at 500 to 600 ° C for 2 to 4 hours under N2 atmosphere, and the calcined product is washed and dried for later use; c. Disperse the powder obtained in step b in the phospholipid solution and stir for 2 to 4 hours, then centrifuge to remove the lower layer of powder and rinse.
2. The catalyst for recycling waste FCC according to claim 1, characterized in that: The mass ratio of template to precursor is 0.5~3:
1.
3. A method for preparing the catalyst according to claim 1, characterized in that: The specific steps of this method are as follows: (1) Pretreatment of spent FCC catalyst: a. Ball-mill the spent FCC catalyst and screen the fine powder below 100 mesh; calcine to remove the coke and other organic impurities adsorbed on the surface; b. The powder obtained in step a and the structure destroying agent are dispersed in deionized water, ultrasonically shaken for 1 to 2 hours, and then stirred and dried at 80 ° C; the resulting mixture is then calcined at 500 to 600 ° C for 2 to 4 hours under N2 atmosphere, and the calcined product is washed and dried for later use; c The powder obtained in step b was dispersed in a phospholipid solution and stirred for 2 to 4h, and then centrifuged to remove the lower layer of powder, rinsed and dried for later use; (2) Precursor and template mixing: The waste FCC catalyst powder pretreated in step (1) and the carbon precursor are dispersed in 50-100° C. deionized water and stirred into a paste; (3) calcining the mixture: calcining the paste mixture obtained in step (2) to obtain a mixture of porous graphite-like carbon nitride and the template; (4) Template primary etching: The mixture obtained in step (3) was dispersed in an excess of acid solution and stirred for 8-12 hours, and then centrifuged and washed to remove the template and heavy metal elements to obtain sample 1; (5) Secondary etching of the template: Sample 1 was dispersed in an excess of hydrofluoric acid solution and stirred for 8-12 h to completely remove the template, followed by centrifugal washing and drying to obtain carbon / phosphorus-doped porous graphite-like carbon nitride.
4. The method according to claim 3, characterized in that: The conditions for pretreatment of spent FCC catalyst are as follows: Step a: the calcination environment is oxygen-rich, the calcination temperature is 500-600°C, and the calcination time is 2-4 hours; The structural destructing agent described in step b is ammonium chloride or ammonium sulfate, and the mass ratio of the structural destructing agent to the powder is 0.5-3:1; The phospholipid solution described in step c is a saturated phosphatidylcholine solution using ethanol as a solvent.
5. The method according to claim 3, characterized in that: The precursor in step (2) is one of cyanamide, dicyandiamide and melamine, and the mass ratio of the graphite-like carbon nitride precursor to deionized water is 1:40-60.
6. The method according to claim 3, characterized in that: The temperature of deionized water in step (2) is 60-80°C.
7. The method according to claim 3, characterized in that: The calcination temperature of step (3) is 500-600°C, the calcination time is 2-4 hours, and the calcination condition is air atmosphere.
8. The method according to claim 3, characterized in that: In the step (4), the acid solution during the primary etching of the template is a 1-5M hydrochloric acid or nitric acid solution, and in the step (5), the hydrofluoric acid solution is a 1-5M hydrofluoric acid solution.
9. Use of the catalyst according to claim 1 in degrading organic matter.
Citation Information
Patent Citations
A method for comprehensive recovery of spent FCC catalysts using hydrochloric acid system
CN111378842B
Method for recovering rare earth La and Ce from FCC dead catalyst
CN111690811A
A method for extracting rare earth elements from spent FCC catalysts by acid leaching coupled with photoreduction.
CN112695213B
Preparation method of porphyrin / carbon nitride layer-by-layer composite structure photocatalytic nano-composite material
CN110961150A
Preparation method of carbon nitride with two-dimensional thin-layer structure
CN110980665A